Requirement of Adult-Born Neurons for Hippocampus-Dependent Learning - Marin Burgin, Antonia (2012)
A fundamental question in the field of adult neurogenesis relies in addressing whether neurons generated in the adult dentate gyrus are needed for hippocampal function. Increasing evidence is accumulating in support of the notion that hippocampus-dependent behaviors activate new neurons and that those neurons are highly relevant for information processing. More specifically, immature new neurons under development that have unique functional characteristics begin to emerge as a highly relevant population in the dentate gyrus network. This review focuses on how hippocampus-dependent behaviors activate adult-born neurons and how modulation and ablation of adult hippocampal neurogenesis alter spatial and associative memory. While several contradictory findings emerge when analyzing the literature, evidence in favor of a relevant role of adult-born neurons in hippocampal function is compelling.